تحليل بعض المتغيرات االبايوكينيماتيكية وبناء اختبار لمهارة سباحة الصدر بالكرة في كرة الماء - وليد غانم (Journal of Sport Science Technology and Physical Activities, 2011)
This paper aimed at: 1- Designing a test for Breaststroke with Ball. Breaststroke 2- Identifying the values of some kinematic variables of . Breaststroke with Ball. 3- Identifying the relation among some bio-kinematic variables of .Breaststroke with Ball. The sample of the study (115 students) was taken from the students of the College of Physical Education in Mosul University, fourth grade, who are (146 students) for the semester 2009-2010, they were chosen intentionally representing 78.767% from the real community of the study The best (11) students were chosen to perform the test. The researcher used the test, technical and scientific observation, measurement and analysis as means to collect data. A video camera was used with a speed of 25 pictures per second to conclude the variables of the research. The researcher used the descriptive approach for its appropriateness to the study, statistical treatments were also used such as (arithmetical mean, standard deviation, simple coefficient of (Pearson). The researcher concluded the following: - There is a positive correlative relation between achievement on the two hand and the total speed of water polo and the average of strike length of swimming with ball - There is a negative correlative relation between the total number of the arm's strikes in water polo on the one side and the average of the time of each strike and the average of a strike length on the other - There is a positive correlative relation between the total number of the arm's strikes on the one side and the average of frequency of each strike and the average of the speed of each strike in Swimming with Ball. - There is a positive correlative relation between achievement and the total number of the strikes in Swimming with Ball. - There is a positive correlative relation between the total speed in water polo and the average of the strike length of the ball - There is a negative correlative relation between the average of strike length on the two hand and the average of strike frequency and the speed of each strike on the other. The researcher recommended a group of recommendations: - For the sake of improving the speed of water polo player frequent strikes should be concentrated on along with the increase of strike length - Concentrating on training in swimming for long and various distances in order to control the ball during swimming - Concentrating on improving the horizontal speed of water polo player along with preserving the ball within the two arms - Paying attention to training on speed tolerance along with the ball and training on ball controlling within the arms - Making further studies on types of swimming with the ball that water polo player needs such as, side swimming with the ball and zigzag swimming